The Local Wisdom of the Acehnese People in Utilizing for Malaria and Asthma Treatment: Kearifan Lokal Masyarakat Suku Aceh dalam Pemanfaatan Tumbuhan Obat Untuk Malaria dan Asma - Rahmah, Eka Nur; Pratama, Al Sira Salsa Madia; Ananda, Aulia; Sholelah, Annisa Mar'atus; Natasyah, Nanda Edlan Putri; Ahmad, Islamudin (Jurnal Riseta Soshum, 2026)
Background: Malaria and asthma remain significant health challenges in Aceh, particularly in rural areas with limited access to modern healthcare. Objective: This study aims to identify and analyze traditional medicinal plants used by the Acehnese people in the treatment of malaria and asthma, focusing on plant parts, preparation methods, and ethnopharmacological relevance. Methods: A narrative review was conducted using primary literature published between 2017 and 2025, retrieved from Google Scholar. Sources were selected based on relevance, completeness, and credibility, and analyzed to identify usage patterns and cultural practices. Results: The findings indicate that Zingiber officinale (ginger) is the most frequently used plant (25%), followed by Piper betle (betel leaf), Acorus calamus (sweet flag), and Psidium guajava (guava). Rhizomes and leaves are the dominant plant parts utilized (40% each), with boiling as the most common preparation method (50%). These practices reflect the community’s local wisdom and empirical knowledge of bioactive compounds. Conclusion: The Acehnese people’s ethnomedicinal practices demonstrate strong potential for the development of standardized herbal medicines. Preserving and documenting local knowledge, while integrating it with modern pharmaceutical approaches, is essential to strengthen culturally rooted and sustainable healthcare systems.